The politics of constitutional nationalism in Northern Ireland, 1932-70 : Between grievance and reconciliation - Norton, Christopher, 1954- (Book collections on Project MUSE., 2014)
In the changed political landscape of Northern Ireland, where all major political parties with a nationalist agenda are now reconciled to the use of peaceful and constitutional means to achieve their objectives, this book presents a timely analysis of the constitutional nationalist tradition in Northern Ireland in the period leading up to the outbreak of the Troubles. The first book on constitutional nationalism to appear in over a decade, this new and incisive work based on extensive primary sources and existing secondary literature, maps the history of the campaigns of nationalist parties and organisations to redress the grievances of Northern Ireland's Catholics and bring partition to an end. It offers a critical reappraisal of these campaigns and it assesses the outcomes and consequences of the political strategies pursued by an array of nationalist parties and groups.